경제의 대외개방도 증가가 숙련 및 미숙련 부문의 고용에 미치는 영향 - 김영준 (12369, 2012)
The second part provides empirical evidence in support of the extension part of the model presented in the first part. Based on the endogenous growth framework as proposed by Romer(1990) and Rivera-Batiz and Romer(1991), the model explains how economic op